ANALISIS SISTEM INFORMASI AKUNTANSI PEMBELIAN KREDIT SPARE PART PT. LILI INDAH PRIMA KARYA - Rahmat Rahmat (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
The purpose of this study was to determine how the implementation of the accounting system of credit purchase spare parts that exist in the company, to know the problems of credit purchases in the company, advising on credit purchase accounting system required by the company. The research was conducted at PT. Lili Indah Karya Prima starting May - June 2015. The procedure adopted to achieve the objective of this study is to decipher and compare between the implementation of accounting information systems Purchase credits spare parts, especially to meet the objective of the internal control system implemented companies with enterprise systems with accounting information systems Credit Purchase spare parts, especially to meet the goal of controlling system intern. From the results of research and analysis has been done, it can be concluded that PT. Beautiful lily Prima Karya has a credit purchase accounting system on the spare parts that support but still require development, existing problems due to a lack of internal control system. Credit purchase system design, adjusted to the functional aspects so as to facilitate the recording.